Efficacy of bath psoralen plus ultraviolet A (PUVA) vs. system PUVA in psoriasis: a prospective, open, randomized, multicentre study. (30th August 2013) - Berneburg, M.; Herzinger, T.; Rampf, J.; Hoetzenecker, W.; Guenova, E.; Meisner, C.; Maetzke, J.; Schaefer, T.; Eberlein, B.; Scharffetter‐Kochanek, K.; Rocken, M.
<x xml:space="preserve">Abstract</x> What's already known about this topic? System photochemotherapy (oral psoralen plus ultraviolet A, system PUVA) is known to be highly effective in psoriasis. What does this study add? There was no significant difference between bath PUVA and system PUVA in treating psoriasis in a prospective, randomized, multicentre trial.